Avaliação dos efeitos de curcumina e silimarina sobre a toxicidade induzida por micotoxinas in vitro e in vivo - Ledur, Pauline Christ (2020)
Mycotoxins are secondary metabolites produced by fungi and represent a worldwide concern due to their global distribution and the harmful effects caused by their ingestion. This problem presents itself in its most dramatic form in farm animals, especially pigs, which are considered the farm animals most sensitive to the effects of mycotoxins. Thus, mycotoxins have been shown to be a serious economic problem, it is essential to elucidate their toxicological mechanisms and seek alternatives that minimize the damage caused by them. In this sense, phenolic compounds and other antioxidants have been shown to have the ability to protect and even neutralize the damage caused by various toxic substances, including mycotoxins. Curcumin and silymarin are two polyphenols known for their strong antioxidant activity extracted from the plants Curcuma longa and Silybum marianum, respectively. In this context, this study aimed to: a) evaluate the toxicity of ochratoxin A (OTA) in pig peripheral blood mononuclear cells and porcine kidney cells of the PK-15 cell line through the evaluation of cell viability, oxidative stress and mitochondrial activity ; b) to evaluate the protective effect of curcumin and silymarin pretreatment on PK-15 cells in vitro on the toxicity induced by OTA, fumonisin B1 (FB1) and deoxynivalenol (DON), via cellular viability assessment, oxidative stress and apoptosis; and c) to investigate the effect of pretreatment with curcumin and silymarin in the prevention of acute toxicity caused by FB1 and OTA on hepatic and kidney oxidative stress, as well as on serological biomarkers of hepatic and kidney function in mice in vivo. We observed that the toxic effects of OTA in PK-15 cells and porcine PBMCs are quite similar, exposure to OTA causes loss of cell viability, increases oxidative stress and causes inhibition of the enzymes superoxide dismutase and catalase, in addition to causing mitochondrial dysfunction , inhibiting complex I of the electron transport chain. Pretreatment with curcumin and silymarin proved to be efficient in protecting PK-15 cells from damage caused by mycotoxins; curcumin decreased the loss of cell viability induced by OTA, FB1 and DON; inhibited the formation of reactive oxygen species triggered by FB1 and DON and decreased apoptosis in cells exposed to DON. The pretreatment of cells with silymarin decreased the loss of cell viability induced by OTA, FB1 and DON; inhibited the formation of reactive oxygen species produced by FB1 and DON and decreased apoptosis in cells exposed to FB1 and DON. In the evaluation of the protective effects of curcumin and silymarin on liver and kidney toxicity caused by OTA and FB1 in mice, it was observed that both compounds, administered alone or in combination, were able to mitigate the harmful effects caused by mycotoxins, promoting improvement in liver and kidney function and preventing oxidative stress, in addition to preventing kidney tubular damage and hepatocyte necrosis caused by exposure to the mycotoxins OTA and FB1. In general, the results of this study demonstrated that both curcumin and silymarin provided protection against the harmful effects caused by exposure to mycotoxins.